PENGARUH KONFLIK PERAN, KETIDAKJELASAN PERAN, DAN KELEBIHAN PERAN TERHADAP KINERJA AUDITOR DENGAN KECERDASAN EMOSIONAL SEBAGAI PEMODERASI (STUDI EMPIRIS PADA KAP DI PEKANBARU, PADANG DAN MEDAN) - Yustiarti, Fenny; Hasan, Amir (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2016)
This study aimed to determine the ability of emotional quotient to moderate the influence of role conflict, role ambiguity and role overload on the auditor performance. Auditors when carrying out field work assignments, doing boundary spanning activity (BSA). Individuals who are at the boundary spanning are potentially experiencing role stress. There are three types of role stress those are role conflict, role ambiguity and role overload. Role conflict, role ambiguity, and role overload would cause stress so that it will degrade performance. An auditors ability to manage emotions is one thing that should be a major concern for the auditor since become one of the key to get out of the pressure so that the auditor can improve the performance. The population in this study were all auditors in a Public Accounting Firm of pekanbaru, medan and padang. The sample was selected using purposive sampling and the hypotheses were tested with moderated regression analysis (MRA). The results show that emotional quotient is able to moderate the influence of role conflict, role ambiguity, and role overload on the auditor performance.